(untitled) (Revista científica Olimpia, 2020)
It is very frequently in some situations or moments of the athlete’s sport life, they turn nervous or excesive pressure due to over physical or psyquis charge that bring about to fulfil a specific goal or take into account an optimum average in whatever sport competition. It’s an answer to the stress that reflect the organism in any external or inner environmental change. That work is in order to apply a system of actions to the treatment of the psychological stress in athletes of the female Softball Team afterwards; in that project were used different methods such as: combined psychotherapy with psychophysiological technics and exercises with the only objective to relieve or avoid the negative effects of the stress in athletes. To the evaluation of the stress were necessary some technics like: IDARE; instrument of the stress evaluation, test through an explanatory study with a pretest and protest design. In fact, with system of actions demonstrated the negative acquisition of the stress in athletes that permits a better comprehension and familiarization of them in relation with the tramning and the competition. As recommendation, it’s necessary to the next investigations take into account the psychological conditions or requirements in any kind of sport that introduce the possibility in the implementation and effectivity of this system.